An Apple Pie for Colonel Sam: The Kitchen, Cooks, and Food of Parkwood Estate, Oshawa, 1917-1973 - Whibbs, Ryan; George, Samantha (Cuizine)

(untitled) (McGill University Library, 2024)
Canada’s Parkwood Estate National Historic Site in Oshawa, Ontario, had a colourful past. Home to the auto-baron McLaughlin family for more than 60 years, the estate played host to events of national and international importance throughout the 1910s-1970s. The food history of this estate has, thus far, remained unpublished. Archival and other evidence indicates that food was a tool used domestically by the McLaughlin family throughout their entertainments, in order to wield increased social status and power. This paper presents, for the first time, details about the mechanics of foodservice in this Canadian Gilded Age estate as well as biographical and professional histories of the cooks who created the food.